2008
DOI: 10.1007/s11064-008-9691-z
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Strategies for Parkinson’s Disease: The Ancient Meets the Future—Traditional Chinese Herbal Medicine, Electroacupuncture, Gene Therapy and Stem Cells

Abstract: In China, it has been estimated that there are more than 2.0 million people suffering from Parkinson's disease, which is currently becoming one of the most common chronic neurodegenerative disorders during recent years. For many years, scientists have struggled to find new therapeutic approaches for this disease. Since 1994, our research group led by Drs. Ji-Sheng Han and Xiao-Min Wang of Neuroscience Research Institute, Peking University has developed several prospective treatment strategies for the disease. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 56 publications
0
29
1
Order By: Relevance
“…Triptolide has also been shown to display a therapeutic effect on solid tumor, leukemia, and a variety of inflammatory disorders, which is often accompanied by increased osteoclast formation (Chen, 2001;Wang et al, 2008;Yang et al, 2003;Yao et al, 2008). Some preclinical in vivo and in vitro studies report that triptolide delays onset of arthritis, lowers the arthritis scores and reduces the expression of osteoclast-activating factors (Hu et al, 2006;Matta et al, 2009;Xiao et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Triptolide has also been shown to display a therapeutic effect on solid tumor, leukemia, and a variety of inflammatory disorders, which is often accompanied by increased osteoclast formation (Chen, 2001;Wang et al, 2008;Yang et al, 2003;Yao et al, 2008). Some preclinical in vivo and in vitro studies report that triptolide delays onset of arthritis, lowers the arthritis scores and reduces the expression of osteoclast-activating factors (Hu et al, 2006;Matta et al, 2009;Xiao et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Previous works have shown that acupuncture and oriental herbal treatments can regulate gene expression that is related to the modulation of intracellular signal transduction and cell development (Shang 2001;Wang et al 2008;Kang 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Han and Wang [39] of the Neuroscience Research Institute of Peking University has developed several prospective treatment strategies for PD. Their studies involve traditional Chinese medicine -herbal formula or acupuncture and modern technologies, such as gene therapy or stem cell replacement therapy.…”
Section: The Anti-inflammatory Effect Of Compounds Isolated From Chinmentioning
confidence: 99%
“…Their studies involve traditional Chinese medicine -herbal formula or acupuncture and modern technologies, such as gene therapy or stem cell replacement therapy. For detailed information, please refer to their recent review [39]. Here we cite an example, the anti-inflammatory effect of triptolide (PG490).…”
Section: The Anti-inflammatory Effect Of Compounds Isolated From Chinmentioning
confidence: 99%